PERAN PROGRAM STUDI TEKNIK PANGAN (FOOD ENGINEERING) UNTUK MENUNJANG PEMBANGUNAN INDUSTRI PANGAN DI INDONESIA [The Roles of Engineering fot the Development of Agro Industries in Indonesia] - Suhargo; Budi Rahardjo (Jurnal Teknologi dan Industri Pangan, 2005)
At this time more than 60 % of Indonesian population still depend on the agricultural sector. Accordingly, in future agro and food industries are expected to be the main steppingstone for the economic development in Indonesia. In order to make the agricultural products competitive in the global market; it is necessary that the development of food or agro industries is supported by technology especially in the food product development and their processing. The food product development consist of food product design, process design, equipment and machinery design and packaging design. Consequently the food product development requires the knowledge of food science, and is necessary to be supported by the knowledge of engineering or know as food engineering. As a course, food engineering is already offered in the study program of food science and technology. However, food engineering is not developed yet as a study program as well as in the other countries, the study program in food engineering is necessarily different from the study program of food science and technology. Food engineering is scientific discipline to study and apply the engineering principles in food preservation, conservation, conversion and distribution. In several countries both study programs are paralely offered as two different study programs with deferent competence and knowledge. The competency of food engineering is mainly in the application of engineering knowledge for food design, design and construction of food process equipment, process design, process equipment operation and management. Accordingly, the content of the food engineering curriculum covers engineering and physics (50-60%), biology and food science (20-30%) and other supporting knowledge’s (statics, communication, etc, 10-20%). The graduates in food engineering will have opportunities working as engineers as well as designing, constructing and operating process equipment in food industries, as researchers and developers of food processes in research institution, as consultant for food industries, or as teaching staff in universities or higher educations. Therefore, study program in food engineering is important to be established. It will significantly support development appropriate technology for agro industries in Indonesia. This study program can be organized together as the study programs in food science and technology and agricultural engineering that already exist in several universities.